Finding Meaning in Disappointment: The Integration of Tafakkur and Tadzakur as Adolescent Emotional Regulation Strategies in Islamic Psychology - Aziz, Akbar Nur; Halim Purnomo; Fuad Nashori; Fitriah M. Suud (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2025)
Disappointment is one of the most prevalent negative emotions experienced by adolescents and can disrupt psychological well-being if not properly managed. This study aims to develop an integrative Islamic model of emotion regulation based on the Qur’anic concepts of tafakkur (cognitive reappraisal) and tadzakkur (spiritual meaning-making). Employing a qualitative approach, this research employed a literature study method and a thematic analysis of Qur’anic verses containing the expressions "la’allakum tatafakkarun" and "la’allakum tadzakkarun."  Data were examined through classical-to-modern interpretations and connected with contemporary psychological theories, including Gross’s emotion regulation framework, Pargament’s religious coping, and Park’s meaning-making model. The findings demonstrated that tafakkur functions as a rational-reflective process that allows individuals to reinterpret disappointment, while tadzakkur strengthens emotional recovery by reconstructing meaning through divine awareness and remembrance. Both serve as complementary mechanisms for cognitive and spiritual regulation, promoting emotional resilience and holistic well-being in Muslim adolescents. This study provides a conceptual contribution to Islamic Psychology by bridging Qur’anic epistemology and modern psychological theory. It also suggests that the integration of tafakkur and tadzakkur can be applied in character education and spiritually-based counseling interventions to help adolescents manage emotional distress constructively.